Does Globalization Lower Wages and Export Jobs? - Slaughter, Matthew (Economic Issues; Economic Issues ;, 1997)
Increased globalization - the international integration of markets for goods, technology, labor, and capital - has coincided in the past 20 years with a shift in demand from less-skilled workers to those with more skills. Have imports from developing countries been responsible for the lowered wages of the unskilled, increased unemployment, and widened income inequality in the more advanced countries? This paper finds that a more important influence on labor markets during these years has been a technology-driven shift in labor demand.